Customer Perception On Security In E-Banking In Malaysia - Parvin, Murshida (2004)
The aim of this research is to evaluate customers' perception on the security of E-Banking in Malaysia. The banking industry is using this new communication media to offer its services to the customers with convenience. This system of interaction between the consumers and the banking industries is called the electronic banking system. Electronic banking or Internet Banking is the use of a computer to retrieve and process banking data such as statements, transaction details, etc.